Providing culturally sensitive diabetes self-management education and support for black African and Caribbean communities: a qualitative exploration of the challenges experienced by healthcare practitioners in inner London. Issue 2 (8th December 2020) - Goff, Louise M; Moore, Amanda; Harding, Seeromanie; Rivas, Carol
Abstract : Introduction: Poor access to, and engagement with, diabetes healthcare is a significant issue for black British communities who are disproportionately burdened by type 2 diabetes (T2D). Tackling these inequalities is a healthcare priority. The purpose of this research was to explore the experiences of healthcare practitioners providing diabetes self-management education and support (DSMES) to African and Caribbean adults living with T2D to inform the development of a culturally tailored DSMES program. Research design and methods: Semi-structured interviews were carried out with a range of healthcare practitioners including diabetes specialist nurses, dietitians and general practitioners based in primary care in inner London. Thematic content analysis was used to identify barriers and facilitators relating to the provision of effective DSMES. Results: Ten interviews were conducted. There was a strong consensus among healthcare practitioners for the importance of DSMES in T2D healthcare. However, practitioners discussed this area of practice as overwhelmingly challenging and recognized a wide range of barriers that they face. Four themes were identified: (1) The tension between structural and responsive care needs, particularly with growing numbers of patients alongside incentivized targets driving a care agenda that does not meet the needs of diverse communities; (2) challenges posed by cultural beliefs and practices, particularly a distrust of conventional medicine, rejection of body mass index standards and a belief in 'God's will'; (3) building relationships through cultural understanding: insiders and outsiders, particularly the benefits of racial concordance and cultural knowledge/resources and (4) getting the messages across, particularly the need to address gaps in structured education. Conclusion: Provision of culturally sensitive DSMES is a challenging area of practice for practitioners, who recognize the need for more training and resources to support them in developing cultural competence. Nonetheless, practitioners recognize the importance of DSMES and are striving to provide culturally sensitive care to their patients.